Effectiveness Analysis of a Semi-Automatic Banana Chips Slicing Machine - Richa Lailil Ulya; Sutopo (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
Bananas are one of the main plantation commodities in Pagerharjo Village, Samigaluh. The local women's farmer group (KWT) processes bananas into chips, but the manual production process creates obstacles because the slices are not uniform. This study aimed to determine the working mechanism of a semi-automatic banana chips slicing machine, identify the most effective test result, and compare production capacity between machine-assisted slicing and manual slicing. The research used a research and development (R&D) method implemented through observation, interviews, problem formulation, product needs analysis, machine performance testing, data collection, and data analysis. Experimental testing was conducted in three blade-gap variations to obtain the most effective slicing result. The machine used a 1/4 hp electric motor with a nominal speed of 1400 rpm. The most effective result was obtained at a 4 mm blade gap, which produced an average slice thickness of 3 mm, 747 g of slices meeting the standard shape from 1 kg of bananas, and a slicing capacity of 27 kg/h.